Detecção de dor neuropática em pacientes com doença falciforme através de questionário de avaliação - Antunes, Fabricio Dias (2017)
Introduction: Sickle cell disease (SCD) is the most common genetic disease in the world. The vaso-oclusion and hemolysis are the central findings of the disease and therefore receive great attention from the scientific community, since the acute painful episodes are very frequent and responsible for a large number of hospital admissions in the country. On the sidelines of this fact so important there are chronic painful conditions that are underestimated or little studied; and perhaps this problem is the definitive diagnosis and appropriate treatment of this disease. Objectives: Identificate through a pain assessment to evaluate the occurrence of neuropathic pain (NP) and discover clinical and epidemiological characteristics of neuropathic pain (NP) in patients with SCD. Methods: A total of 554 patients, 56 were recruited from university outpatient service, which is a regional reference for the treatment of NP, and a cross-sectional study conducted between July 2015 and March 2016, after established inclusion and exclusion criteria. The instrument used in this study was to NP detection range Leeds assessment of neuropathic symptoms and signs (LANSS). Demographic and clinical data were extracted from patient records and during the interview. The scales were applied according to the rules of its creators to detect evidence of NP. Chi-square test or Fisher's exact test were applied to compare the groups with and without NP depending on variables: teens (14-18 years) versus adults (19-32 years), sex and use of hydroxyurea. Age values were compared in patients with and without NP through ANOVA and Kruskal-Wallis tests, considering significant p values <0.05. Results: The average overall age was 20.6 years and 51.8% were male. The most common site of pain is the lower back (53.6%). 14 patients (25%) had evidence of NP. Age was positively correlated with NP, with higher rates among adults compared to teens (92.9 versus 7.1%; p < 0.01). The mean age compared in the presence or absence of NP is also significantly higher than in the first group (p < 0.05). There was a positive association between patients using hydroxyurea and presence of NP (71.4 versus 28.6%; p < 0.05). An association was observed between the presence of sensory changes identified through physical LANSS the mini-exam and final score of the corresponding LANSS the NP (p < 0.01). None of the identified patients had any treatment for NP. Conclusion: In a simple way you can establish the diagnosis of NP in SCD holders and to identify the clinical and epidemiological profile of this group.